Applicability of focused Ion beam (FIB) milling with gallium, neon, and xenon to the fracture toughness characterization of gold thin films - Preiß, Eva; Merle, Benoit; Xiao, Yuan; Gannott, Florentina; Liebig, Jan Philipp; Wheeler, Jeffrey M.; Göken, Mathias (Journal of Materials Research, 2021)
Abstract: Focused ion beam (FIB) milling is an increasingly popular technique for fabricating micro-sized samples for nanomechanical characterization. Previous investigations have cautioned that exposure to a gallium ion beam can significantly alter the mechanical behavior of materials. In the present study, the effects of gallium, neon, and xenon ions are scrutinized. We demonstrate that fracture toughness measurements on freestanding gold thin films are unaffected by the choice of the ion species and milling parameters. This is likely because the crack initiation is controlled by the local microstructure and grain boundaries at the notch, rather than by the damaged area introduced by FIB milling. Additionally, gold is not susceptible to chemical embrittlement by common FIB ion species. This confirms the validity of microscale fracture measurements based on similar experimental designs. Graphical abstract: [Figure not available: see fulltext.].
CRIS-Team Scopus Importer:2021-03-05

Funktionelle Beschichtungen in der Nanotechnologie - Ein Kooperationsprojekt Schule-Hochschule. - Heinzerling, Peter; Dräger, Gerald; Kometz, Andreas; Preiß, Eva (Praxis der Naturwissenschaften - Chemie in der Schule, 2015)
Es werden Experimente zur Funktionalisierung von Oberflächen vorgestellt. Neben der Beschichtung kommt es auch zu chemischen Reaktionen an der Oberfläche, was zu veränderten Eigenschaften führ
Keywords: Schule; Experiment; Beschichtung; Chemieunterricht; Kunststoff; Nanochemie; Partikel; Projekt; Nanotechnologie; Hochschule; Kooperation; Deutschland

Mechanical characterization of metallic thin films by bulge and scratch testing - Javed, Hassan; Merle, Benoit; Preiß, Eva; Hivet, Romain; Benedetto, Alessandro; Göken, Mathias (Surface & Coatings Technology, 2016)
The mechanical properties of 20-nm thick silver, titanium and nickel-chromium alloy films encapsulated between two silicon nitride ceramic layers are investigated by bulge and scratch tests. Bulge tests are used in order to measure the yield strength of the metallic films. An unexpected strain-softening behavior is observed for a silver sample, which is rationalized as a measurement artifact due to the delamination of the film from its substrate. An experimental workaround is proposed and shown to yield correct measurements. The adhesion strength of the metallic films is measured by scratch tests, and their failure mechanism is characterized by in-situ optical observations. All in all, the poorest mechanical properties are found in the silver. This is probably due to a combination of the low adhesion at the interface between the nitride and the metal and the low yield stress of the silve
Keywords: Bulge test; Scratch test; Silicon nitride; Silver; Thin film

Microstructural dependence of the fracture toughness of metallic thin films: A bulge test and atomistic simulation study on single-crystalline and polycrystalline silver films - Preiß, Eva; Lyu, Hao; Liebig, Jan Philipp; Richter, Gunther; Gannott, Florentina; Gruber, Patric A.; Göken, Mathias; Bitzek, Erik; Merle, Benoit (Journal of Materials Research, 2019)
The microstructure contribution to the very low fracture toughness of freestanding metallic thin films was investigated by bulge fracture tests on 200-nm-thick 100 single-crystalline and polycrystalline silver films. The single-crystalline films exhibited a significantly lower fracture toughness value (KIC = 0.88 MPa m1/2) than their polycrystalline counterparts (KIC = 1.45 MPa m1/2), which was rationalized by the observation of an unusual crack initiation behavior - characterized by twinning in front of the notch tip - during in situ testing in the atomic force microscope. Twinning was also observed as a dominant deformation mechanism in atomistic simulations. This twinning tendency is explained by comparing the resolved shear stresses acting on the leading partial dislocation and the full dislocation, which allows to develop a size- and orientation-dependent twinning criterion. The fracture toughness of polycrystalline samples was found to be higher because of the energy dissipation associated with full dislocation plasticity and because of crack meandering along grain boundaries.
CRIS-Team Scopus Importer:2019-09-27
Keywords: atomistic simulations; bulge testing; fracture testing; grain boundaries; silver; thin films; twinning criterion

Scaling of the fracture toughness of freestanding metallic thin films with the yield strength - Preiß, Eva; Gannott, Florentina; Göken, Mathias; Merle, Benoit (Materials Research Letters, 2018)
The influence of the yield strength on the fracture toughness of freestanding metallic films with a thickness of similar to 150 nm was investigated by bulge testing. For this purpose, gold films prepared by thermal evaporation were tested at room temperature and at 100 degrees C. Additionally, different Au-Ag solid-solution strengthened films were studied. The fracture toughness of the films is observed to increase with increasing yield stress. This is at first sight counterintuitive but can be explained by previously observed severe necking leading to a chisel-point type of fracture in freestanding metallic thin films.[GRAPHICS]IMPACT STATEMENTFreestanding metallic thin films exhibit an extremely low fracture toughness. It is shown in this publication that Kic can be significantly improved by increasing the yield strength of the films.
Keywords: Fracture toughness; thin films; AuAg solid solutions; bulge test

Understanding the Extremely Low Fracture Toughness of Freestanding Gold Thin Films by In-situ Bulge Testing in an AFM - Preiß, Eva; Merle, Benoit; Göken, Mathias (Materials Science and Engineering A-Structural Materials Properties Microstructure and Processing, 2017)
The fracture toughness of freestanding gold films with thicknesses between 60 nm and 320 nm was determined by bulge testing to be around 2 MPa m1/2. This surprisingly low value confirms the trend also observed for other metals that thin films exhibit only a fraction of the bulk fracture toughness. In order to understand this behavior, the fracture process of freestanding gold films with a crack introduced by focused ion beam (FIB) milling was observed in-situ in an atomic force microscope (AFM). AFM scans of the crack tip region show stable crack growth mainly along grain boundaries. Plastic deformation is localized in a narrow corridor in front of the crack tip. A large plastic zone, as one would typically expect under plane stress, is not observed. Instead, strong local necking is evidenced. We conclude that the spatial confinement of the plastic deformation is the primary reason for the low fracture toughness of metallic thin film
Keywords: Fracture toughness; Thickness effect; Thin films; Bulge testing; Atomic force microscopy; Gold